Head Injury is the most common cause of death due to Road Traffic Accident - Ahmed, Khan Shakil; Saha, Sanjoy; Haque, Syed Didarul (Mediscope, 2022)
In developing countries including Bangladesh injuries and deaths due to Road Traffic Accident (RTA) are appeared to be major and alarming problems and it requires noticeable measures and efforts for prevention of morbidity and mortality rate. The objective of present study was to investigate the pattern of injuries in RTA. This descriptive cross-sectional study was conducted among the victims who died of RTA from 2006 to 2012 and were autopsied at Dhaka Medical College Morgue. Among 1000 cases of death due to RTA, the numbers of deaths only due to head injuries are 472, the numbers of death due to head & other injuries are 272 & the numbers of deaths only due to other injuries are 256. According to this study head injury is the most common cause of death due to RTA & which is about 47.2%. Mediscope 2022;9(1): 5-8